Bench-top comparison of thermometers used in newborn infants. Issue 4 (28th December 2020) - Dunne, Emma A; Cunningham, Katie; O'Donnell, Colm Patrick Finbarr; McCarthy, Lisa K
Abstract : We wished to determine the accuracy of thermometers used to measure temperature in newborn infants. We measured the temperature of a water bath with three types of thermometer set at 0.5°C increments between 32.5°C and 38.5°C and compared the values to a control. We recorded the time to display steady-state temperature. The Microlife thermometer most closely approximated control temperature (mean difference <0.1°C (SD<0.1°C)) and displayed a reading in a mean time of 29 s (SD 2 s). Used in 'predictive' (default) mode, the Welch Allyn SureTemp Plus 692 thermometer differed from the control by a mean of 0.6°C (SD 0.3°C), displaying a temperature at 15 s (SD 3 s). This device consistently overestimated temperature. In 'continuous' mode, the mean difference was <0.1°C (SD<0.1°C) at 5 min. The Phillips probe differed from the control by a mean of 0.4°C (SD 0.2°C). Thermometers used to measure temperature in newborn infants may underestimate hypothermia. A prospective study in newborn infants is needed.